2013
DOI: 10.1038/eye.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

Intensive cataract training: a novel approach

Abstract: Purpose To evaluate the safety of an intensive cataract surgery training programme. Methods An intensive cataract surgery training programme was implemented in August 2010 for year 3 ophthalmology trainees in the East Midlands Deanery North Rotation (United Kingdom). Trainees participated in extra-ocular surgery and 50 h of virtual reality cataract surgery simulator training over a 2-year period. Their third year comprised 6 months of intensive phacoemulsification training in a tertiary centre followed by a 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Recently, Baxter et al 22 evaluated the outcomes of implementing a 2 year intensive cataract surgery training programme on a total of three residents. The programme comprised 50 h virtual reality surgical simulator training (EYESi) and performing a minimum of 250 cataract surgeries as a primary surgeon within the 2 year period of the programme (150 cases in the first 6 months).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Baxter et al 22 evaluated the outcomes of implementing a 2 year intensive cataract surgery training programme on a total of three residents. The programme comprised 50 h virtual reality surgical simulator training (EYESi) and performing a minimum of 250 cataract surgeries as a primary surgeon within the 2 year period of the programme (150 cases in the first 6 months).…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, individual learning curves have been only casually analyzed [5] [7] . This places the recent proposal of the German Ophthalmological Society (GOS) in a tenuous position: the GOS recently recommended, that the first 300 cataract surgeries should generally be performed under supervision.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the overall intraoperative complication rate (15.12%) was in the upper normal range reported elsewhere (1.8 % to 15%) [5][6][7][8][9][10][11][12] . Th is could be explained by the fact that half of the trainees (4/8) were at the very beginning of the operating learning curve, having only wet lab experience.…”
Section: %mentioning
confidence: 62%
“…Unfortunately, even though ophthalmology residents in foreign countries spend a large proportion of their surgical training learning cataract surgery 3 , in our country it was not common practice 4 . As many previous studies showed that complication rates and outcomes of cataract surgery performed by residents were acceptable [5][6][7][8][9][10][11][12] , it was decided to start fi rst resident phacoemulsifi cation-learning program at the Clinical Department of Ophthalmology, Sestre milosrdnice University Hospital Center. Th e purpose of this pilot study was to analyze the resident learning process of phacoemulsifi cation cataract surgery at the Clinical Department of Ophthalmology, Sestre milosrdnice University Hospital Center, and to assess the resident phacoemulsifi cation learning curve in order to implement cataract surgery training into the residency program in the future.…”
Section: Introductionmentioning
confidence: 99%